2018
DOI: 10.12890/2018_000855
|View full text |Cite
|
Sign up to set email alerts
|

Catatonia and Psychosis as Manifestations of Primary Sjögren’s Syndrome

Abstract: Primary Sjögren’s syndrome (SS) is a chronic, systemic autoimmune disease, most commonly presenting with sicca symptoms—xerostomia and xerophthalmia. Up to one-half of affected individuals also develop extra-glandular involvement. Early diagnosis is important to prevent further complications. This paper describes an atypical case of SS in a 21-year-old woman who presented first with neuropsychiatric symptoms and fever. She was diagnosed and treated for a presumed psychotic episode. However, because she remaine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 5 publications
2
12
0
Order By: Relevance
“…SPECT assessment should be considered, as it revealed a hypoperfusion in parietal, temporal, and frontal lobes in more than 50% of patients having normal MRI brain when cognitive dysfunction was present. This SPECT pattern was present only in 17% of pSS patients without cognitive dysfunction [20,21,22,23,24,25,26,27,28,29,30,31,32,33,34,35,36,37,38,39,53].…”
Section: Discussionmentioning
confidence: 99%
“…SPECT assessment should be considered, as it revealed a hypoperfusion in parietal, temporal, and frontal lobes in more than 50% of patients having normal MRI brain when cognitive dysfunction was present. This SPECT pattern was present only in 17% of pSS patients without cognitive dysfunction [20,21,22,23,24,25,26,27,28,29,30,31,32,33,34,35,36,37,38,39,53].…”
Section: Discussionmentioning
confidence: 99%
“…Psychiatric abnormalities have also been described including depression, anxiety, and cognitive deficits [3]. Psychosis has been reported in adult patients [3,[7][8][9][10][11][12] with pSS but has never been previously reported in the pediatric literature, although other psychiatric manifestations including major depressive disorder and obsessive compulsive disorder (OCD) have been described in pediatric patients [13].…”
Section: Introductionmentioning
confidence: 99%
“…The therapeutic course suggested that catatonia with depressive episodes was a consequence of SS pathology. Although psychiatric symptoms have been commonly reported in SS [ 3 ], to the best of our knowledge, only one case of catatonia comorbid with SS has been previously reported [ 9 ].…”
Section: Discussionmentioning
confidence: 99%